Pengaruh Ukuran Usaha dan Pengetahuan Akuntansi terhadap Penerapan Pencatatan Keuangan UMKM (Studi Kasus pada Konveksi Pakaian Muslim di Nagari Batu Taba) - Dulva Hendra; Zulhelmi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. Business size is one of thedetermining factors in thesustainability of MSMEs, one of which is the implementation of recording financial reports, as well as accounting knowledge, where accounting knowledge is very important for knowing and evaluating current business developments, as well as planning for the next period. Therefore, theaim of this research is todetermine the influenceof business size andaccounting knowledge onthe implementation ofMSME financial records. Questionnaires were a datacollection technique usedin researchwith a total of40 respondents in theMuslim clothing convection business in Nagari Batu Taba. Multiplelinear regression analysis isthe data analysismethod used, andSPSS 25 is used to process the data. Withthe t-calculated value obtained at 0.036 < 2.024 and the sig value at 0.971 > 0.05, thepartial researchfindings show that business size does not have a positive and significant influence on the implementation of MSME financial records. Accounting knowledge has a positive and significant influence on the application of financial recording, as evidenced by the t-value of 2.698 > 2.024and a sig value of 0.010< 0.05. Business size and accounting knowledge have a positive and significant effect on the implementation of financial recording, seen from the results of the f test with a calculated f value of 5.135 > 3.24 and a sig. equal to 0.011 < 0.05. The test findings produced a coefficient of determination (R2) of 0.217 or 21.7%. This shows that business size and accounting knowledge have an influence of 28.3% on the implementation of MSME financial recording, while the remaining 78.3% is influenced by other factors.